High nuc DNA load in whole blood is associated with sepsis, mortality and immune dysregulation in Staphylococcus aureus bacteraemia. Issue 3 (4th March 2019) - Ziegler, Ingrid; Cajander, Sara; Rasmussen, Gunlög; Ennefors, Theresa; Mölling, Paula; Strålin, Kristoffer
Abstract: Background: Staphylococcus aureus bacteraemia is a disease with varying presentation, ranging from uncomplicated to life-threatening infections. In S. aureus bacteraemia, a high load of bacterial DNA in blood has been linked to mortality. We hypothesized that a high DNA load would also be linked to the presence of sepsis, and to high C-reactive protein (CRP) and lymphopaenia, indicating inflammation and immunosuppression. Methods: Twenty-seven patients with culture-proven S. aureus bacteraemia, 13 (48%) with sepsis and six (22%) non-survivors, were enrolled in a prospective study. Blood samples were collected on days 0, 1–2, 3–4, 6–8, 13–15 and 26–30, and subjected to droplet digital PCR targeting the nuc gene to determine the nuc DNA load. Results: nuc DNA was detected on days 0–2 in 22 patients (81%), and on days 6–8 in three patients (all non-survivors). The nuc DNA load on days 1–2 was significantly elevated in patients with sepsis (median 2.69 versus 1.32 log10 copies/mL; p = .014) and in non-survivors (median 2.5 versus 1.0 log10 copies/mL; p = .033). Patients with a high nuc DNA load (>3.0 log10 copies/mL) on days 1–2 had significantly elevated CRP levels at all timepoints, and significantly decreased lymphocyte counts on days 0, 1–2, 13–15 and 26–30. Conclusions: Our results indicate that a high initial load of S. aureus DNA in blood is associated with sepsis, mortality and persistent immune dysregulation in S. aureus bacteraemia patients. Further studies are needed to define the role of bacterial DNA load monitoring in the management of S. aureus bacteraemia.